2022
DOI: 10.2147/dmso.s377720
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Low-Carbohydrate, High-Fat Diet versus Moderate-Carbohydrate and Fat Diet on Body Composition in Patients with Lipedema

Abstract: Lipedema is a disorder characterized by an excessive accumulation of subcutaneous body fat, mainly bilateral and symmetrical accumulation of fat deposits, particularly in the lower extremities excluding feet. Pain (spontaneous or with palpation) and increased capillary fragility with bruising are also part of clinical presentation. It is estimated to occur in approximately 11.0% of women worldwide. Management of obesity among patients with lipedema is a key component in its treatment. Purpose: The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
0
23
0
3
Order By: Relevance
“…Eine Studie aus Norwegen bestätigt dies und ergänzt: Sobald nach Low Carb eine kohlenhydratreichere Erhaltungsdiät einsetzt, kommen die Beschwerden trotz Gewichtserhalt zurück 5 . Eine andere Studie vergleicht erstmals zwei Diäten mit verschieden starker Kohlenhydrate Einsparung 6 . Low Carb erscheint hier deutlich wirksamer für Körpergewicht, Körperumfänge und Symptomatik.…”
Section: Aktuelle Studienlageunclassified
“…Eine Studie aus Norwegen bestätigt dies und ergänzt: Sobald nach Low Carb eine kohlenhydratreichere Erhaltungsdiät einsetzt, kommen die Beschwerden trotz Gewichtserhalt zurück 5 . Eine andere Studie vergleicht erstmals zwei Diäten mit verschieden starker Kohlenhydrate Einsparung 6 . Low Carb erscheint hier deutlich wirksamer für Körpergewicht, Körperumfänge und Symptomatik.…”
Section: Aktuelle Studienlageunclassified
“…Eine andere Studie aus Polen verglich erstmals zwei Diäten mit verschieden starker Kohlenhydrat-Einsparung 7 . Low Carb erscheint hier deutlich wirksamer für Körpergewicht, Körperumfänge und Symptomatik.…”
Section: Aktuelle Studienlageunclassified
“…Eine weitere polnische Studie ohne randomisierte Diätzuteilung zeigte bei Lipödem-Patientinnen unter Low-Carb-Behandlung teils bessere oder unveränderte metabolische Parameter, aber auch partiell verschlechterte Glukose- und LDL-Werte 8 . In der weltweit ersten (aus Russland stammenden) randomisiert-kontrollierten Studie zum Vergleich verschiedener hypokalorischer Diäten schneiden Low Fat und Low Carb nach 4 Wochen vergleichbar ab, mit Benefits für Körpergewicht und Stoffwechsel.…”
Section: Aktuelle Studienlageunclassified
“…Obesity often co-occurs with lipedema [1, 9,10]. In our previous study, we demonstrated that 78% of patients with lipedema were overweight or obese based on the body mass index (BMI) [11]. Management of existing overweight or obesity is essential in lipedema treatment [1,2,6,7,11].…”
Section: Introductionmentioning
confidence: 99%